Immune Assisted Tissue Engineering via Incorporation of Macrophages in Cell-Laden Hydrogels Under Cytokine Stimulation - Barthes, Julien; Dollinger, Camille; Muller, Celine B.; Liivas, Urmas; Dupret-Bories, Agnes; Knopf-Marques, Helena; Vrana, Nihal E. (Frontiers in Bioengineering and Biotechnology, 2018)
The function of soft tissues is intricately linked with their connections with the other systems of the body such as circulation, nervous system and immune system. The presence of resident macrophages in tissues provide a means to control tissue homeostasis and also a way to react physical/biological insults and tissue damage. Thus, incorporation of resident macrophage like, phenotype-controlled macrophages in engineered tissues can improve their fidelity as model tissues and also improve their rate of integration and facilitate the resolution of inflammation for regenerative medicine applications. Herein, we demonstrate two potential ways to immunoassist the remodelling process of engineered soft tissues in 3D gelatin-based hydrogels containing fibroblasts and/or endothelial cells i) with supplementation of IL-4 in the presence of macrophages and ii) in tri-culture via naive monocytes or differentiated macrophages. The presence of IL-4 had a proliferative effect on fibroblasts with a significant boosting effect on proliferation and cytokine secretion in the presence of differentiated macrophages with an upregulation of activin, IL-1RA, TNF alpha and IL-1beta creating a more stimulating microenvironment. The addition of IL-4 in endothelial macrophage co-culture configuration improved the organization of the sprout-like structures with a boost in proliferation at day 1 and with the upregulation of IL-6, IL-1RA at the earliest stage in the presence of differentiated macrophages creating a favorable microenvironment for angiogenesis. In tri-culture conditions the presence of monocyte or macrophages resulted in a denser, tissue like structures with highly remodeled hydrogels. The presence of differentiated macrophage had a boosting effect on the angiogenic secretory microenvironment such as IL-6, IL-8 without any additional cytokine supplementation. The presence of fibroblasts in combination with endothelial cells had also a significant effect on the secretion of angiopoietin. Our results demonstrate that incorporation of macrophages in a resident macrophage function and their phenotype control had significant effects on the maturation and cytokine microenvironment of 3D multiple cell type-laden hydrogels which can be harnessed for better integration of implantable systems and for more physiologically relevant in vitro tissue models with an immune component.